2018
DOI: 10.1016/j.lrr.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

High-dose methotrexate vs. Capizzi methotrexate for the treatment of childhood T-cell acute lymphoblastic leukemia

Abstract: Sixty-three children (1–14 years of age) newly diagnosed with T-cell acute lymphoblastic leukemia were treated from January 2001 to December 2014. Patient outcomes were evaluated based on the regimen received; Capizzi methotrexate (C-MTX) vs. high-dose methotrexate (HDMTX). Complete remission (CR) was achieved in 54 of 60 (90.0%) patients and 3 patients died during induction. The 5-year overall survival (OS) and disease-free survival (DFS) were 88.3 ± 6.5% and 85 ± 7.5%, respectively. Post-induction, 35 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This finding was mainly related to a higher cumulative incidence of remission deaths in females receiving high intensity regimens (Arm B and C regimens). The cause for gender related differences in treatment related toxicity is not clear, but may be due to gender-related pharmacokinetic differences suggested in our population [26]. Our observations are supported by those reported by the Children’s Oncology Group study that showed a higher likelihood of treatment-related death in females undergoing treatment for high-risk ALL [27].…”
Section: Discussionsupporting
confidence: 87%
“…This finding was mainly related to a higher cumulative incidence of remission deaths in females receiving high intensity regimens (Arm B and C regimens). The cause for gender related differences in treatment related toxicity is not clear, but may be due to gender-related pharmacokinetic differences suggested in our population [26]. Our observations are supported by those reported by the Children’s Oncology Group study that showed a higher likelihood of treatment-related death in females undergoing treatment for high-risk ALL [27].…”
Section: Discussionsupporting
confidence: 87%
“…The poor response of patients with t (1;19) ALL in our population was different from that reported by COG and merits further study. The inferior survival observed in female ALL patients also suggests a population difference . Pharmacokinetic/pharmacogenomic differences by gender could account for this.…”
Section: Discussionmentioning
confidence: 99%
“…9 The expression of multidrug resistance gene polymorphisms, like ABCC2, affects folate metabolism and causes MTX toxicity. The ALT levels have remained a surrogate marker to assess toxicity in the study by Jastaniah et al 5 The highest value of ALT documented in our study was 812 U/L, none of the children developed deranged prothrombin time (PT)/activated partial thromboplastin time (APTT) or signs of liver failure. Ursodeoxycholic acid was routinely used in children with elevated transaminases and response to therapy in the form of decreasing trend of liver enzymes was documented in 100% of the children.…”
Section: Discussionmentioning
confidence: 50%
“…The other studies which have shown comparable results of the Capizzi and HD MTX in T ALL have utilized an intensified intrathecal therapy up to 28 doses in males and 21 doses in females. 5 Thus, the Capizzi regimen is increasingly gaining importance in various aspects of ALL management. Reports of comparable toxicity and ease of administration of HD MTX regimens exist, while the literature on toxicity encountered with the Capizzi MTX has been addressed by very few studies in the past.…”
Section: Discussionmentioning
confidence: 99%